2020
DOI: 10.1002/hpja.347
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and health care interventions: Substantiating a multi‐modal challenge through the lens of grounded theory

Abstract: Issue addressed: One of the biggest concerns for human health in the 21st century is the ever-increasing rate of obesity and its associated budgetary implications for publicly funded health care service provisioning. This study at the outset explores the multifaceted nature of food-related consumption choices and outcomes of obesity, and later offers suggestions to improve the existing interventional strategies to curtail the epidemic. Methods: A total of 24 participants were recruited through poster invitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Further, obese working-aged individuals were adviced almost three times more often to change their health behavior and participated 1.5 times more often in health-promoting programs such as smoking cessation and weight-loss program which also reflects the number of given interventions. In a study of New Zealand, it was also found that current health care interventional programs are not effective enough in means of reducing obesity and that new and broader perspectives should be encouraged if positive results were expected [14]. Contrarily, implementing health promotion programs has been suggested to reduce healthcare costs by employees with high blood glucose, obesity, stress, depression, and physical inactivity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Further, obese working-aged individuals were adviced almost three times more often to change their health behavior and participated 1.5 times more often in health-promoting programs such as smoking cessation and weight-loss program which also reflects the number of given interventions. In a study of New Zealand, it was also found that current health care interventional programs are not effective enough in means of reducing obesity and that new and broader perspectives should be encouraged if positive results were expected [14]. Contrarily, implementing health promotion programs has been suggested to reduce healthcare costs by employees with high blood glucose, obesity, stress, depression, and physical inactivity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a multifactorial chronic disease influenced by various biological factors (e.g., genetic, medical), psychological factors, and situational factors that contribute to Nutrients 2024, 16, 949 2 of 18 its development and persistence [1,5,[7][8][9]. One potentially crucial aspect implicated in the development and persistence of obesity is the idea that certain foods may trigger a dependency response in some individuals [10][11][12]-namely, food addiction (FA).…”
Section: Introductionmentioning
confidence: 99%
“…Following the conclusion of the COVID-19 period, the most significant thing that will be on the post-COVID-19 agenda in many countries across the world is to work toward improving the people's diets and, as a result of this, the health of such populations. It is regarded as how one can live a healthy lifestyle and tackle the ever-increasing problem of being overweight and obese (Gaur et al, 2020;Kliment et al, 2021;Mandlik et al, 2021) . According to the research conducted in the past, this may be accomplished by placing individual responsibility for one's health care (Martindale et al, 2020;Király et al, 2020;Overgaauw et al, 2020).…”
Section: Introductionmentioning
confidence: 99%